Demand Sphere as a Co-engine of Sustainable Development - Cialowicz, Beata (European Journal of Sustainable Development, 2017)
This work is coherent with currently active research path which emphasizes the active role of consumers in economic development and with the idea that economic evolution is an immensely complex process, especially with the fact that the demand side plays an important active role in making the development sustainable. In this process eco-innovations are important from an environmental and social perspective, concerning the achievement of long run sustainable growth patterns. In this sense, understanding the specific social and technological processes is very important in designing policies towards sustainable growth. Hence the main aim of this paper is to give theoretical account of the process of economic development based on eco-innovations and demonstrate that consumer sphere is a co-engine of sustainable development of the whole economy. In particular it will be proved that consumers with environmental-friendly preferences may shape technological trajectories to improve the diffusion of eco-innovations. The study is coherent with previous modelling of Schumpeterian innovative evolution in the formal apparatus of modern (dynamic) Arrow-Debreu theory of general equilibrium. Research results will take the form of mathematical theorems interpreted from an economic perspective and each argument will have a form based on formal deduction. Keywords: innovations, Arrow-Debreu model, demand sphere,